Penyelesaian Kasus Perzinaan Dalam Keluarga - Hidayat, Iman (Legalitas: Jurnal Hukum, 2024)
This paper discusses the settlement of adultery cases in the family. The formulation of this problem is how the settlement of adultery cases in the family, what are the problems encountered and how to overcome them. To analyse these problems, a Socio Legal Research approach is used, which is research that refers to the legal norms contained in the applicable laws and regulations and is then associated with the application that occurs in the community.To examine the three existing problems, several theories are used, among others, the theory of restorative justice, crime prevention, customary law. The results of this study indicate that the settlement of adultery cases in the family is carried out by customary criminal law derived from the basis of Jambi customary law, namely by expulsion from the village but previously held a village wash by giving one buffalo, 100 bushels of rice, 50 coconuts and as sweet as possible. Then the perpetrator apologised for his actions and signed a peace agreement (Surat setih). The problems encountered were that there was a difference of opinion between the youth and the tengganai elders in the adat meeting in deciding on the sanction of this case, adultery cases resolved by national criminal law were time consuming and costly, causing much suffering to the perpetrator, the community does not know much about the basis of Jambi Customary Law. Efforts to overcome the problems that occur include holding a personal approach from the youth with the elders of the tengganai to continue to apply the existing criminal law, all parties deliberate that customary criminal law is more appropriate than national criminal law, providing socialisation to the community so that they know the basis of Jambi customary law. The suggestion is that in order to prevent adultery in the family, namely providing religious counselling so that faith is strengthened rather than lust and counselling on the basis of Jambi customary law so that people know that customary criminal law can resolve cases of family adultery quickly, affordable costs, thus the existence of customary criminal law applies and has permanent legal force.